2009
DOI: 10.1287/mnsc.1090.1042
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Model for Posttraumatic Stress Disorder Among U.S. Troops in Operation Iraqi Freedom

Abstract: We develop a dynamic model in which Operation Iraqi Freedom (OIF) servicemembers incur a random amount of combat stress during each month of deployment, develop posttraumatic stress disorder (PTSD) if their cumulative stress exceeds a servicemember-specific threshold, and then develop symptoms of PTSD after an additional time lag. Using Department of Defense deployment data and Mental Health Advisory Team PTSD survey data to calibrate the model, we predict that-because of the long time lags and the fact that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Gates et al (2012) refer to results which show that 226,000 individuals serving in OEF (active Operation Enduring Freedom, Afghanistan and Operation Iraq freedom) had been diagnosed with PTSD by 2007. Atkinson et al (2009) predict in their model that the number of affected will have increased to 313,000 by 2023. The picture is the same for troops in the UK (Ministry of Defence, UK 2013).…”
Section: Current Situationmentioning
confidence: 99%
“…Gates et al (2012) refer to results which show that 226,000 individuals serving in OEF (active Operation Enduring Freedom, Afghanistan and Operation Iraq freedom) had been diagnosed with PTSD by 2007. Atkinson et al (2009) predict in their model that the number of affected will have increased to 313,000 by 2023. The picture is the same for troops in the UK (Ministry of Defence, UK 2013).…”
Section: Current Situationmentioning
confidence: 99%
“…In a recent study by the Department of Veterans Affairs (VA), close to 30% of 834,463 Iraq/Afghanistan veterans seen at VA facilities had PTSD [32], and PTSD rates among these veterans may reach approximately 35% [33]. …”
Section: Posttraumatic Stress Disordermentioning
confidence: 99%
“…Symptoms can vary widely, be difficult to treat, and be functionally debilitating (Buckley et al, 2000; Rubin et al, 2008; Vasterling and Verfaellie, 2009). More than 20% of returning OEF/OIF military personnel present with PTSD (Hoge et al, 2004), much higher than the 6% reported in the civilian population (Kessler et al, 2005), and this prevalence is increasing (Atkinson et al, 2009). …”
Section: Introductionmentioning
confidence: 96%